The Empowered : a Trevor Black Novel - Parshall, Craig 1950- (Thorndike, Maine : Center Point Large Print, 2018)
"Craig Parshall delivers supernatural suspense for today's readers, along with legal suspense elements that will appeal to his core readers. This story is for readers of Frank Peretti, Randy Singer, Ted Dekker, and Steven James"--
Keywords: Paranormal fiction; Large type books; Suspense fiction